A Strategic Supply Chain Approach: Consortium Marketing in the Italian Leatherwear Industry - Guercini, S.; Woodside, Arch (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to describe inter-firm marketing cooperation as a strategy by small and medium enterprise (SME) players in local systems of fashion firms. Design/methodology/approach – This case study research focuses on Italian leatherwear manufacturers that join together to create an interfirm consortium which acts as a sole manufacturer-marketing player. Findings – The case study observes marketing policy orientations toward the final consumers while remaining consistent with the aim of preserving cooperation with the big international retail buyers. The comprehensive description provides propositions relevant for advancing a theory of interfirm cooperation and marketing behavior. The paper reports on implementing consortium marketing through the integration of marketing activities among the SMEs in the Italian fashion leatherwear industry. Research limitations/implications – Consortium marketing (CM) organizations represent one structure among several for the coordination of activities by independent firms in a supply chain; CM usually includes planned collaboration in innovation processes in creating and adopting superior technologies, designing products highly desired by customers, and manufacturing to meet the demands greater than the production capability of any one member are common characteristics of CM organizations.Practical implications – “Consortium marketing” has special strengths that this paper describes and explains. Creating inter-firm structures to achieve marketing synergies is the core objective of CM. CM can be a very powerful structure for supply chains for achieving multiple synergies in innovating, designing, manufacturing, promoting, and/or delivering of products and services to their immediate customers and downstream customers. Originality/value – Inter-firm design and relationships need not be a given; firms participating in CM can innovate their inter-firm relationships to achieve synergies that may be impossible to achieve otherwise. This paper is the first to offer this conclusion and describe its applicability within the high-fashion Italian leatherwear industry.